2019
DOI: 10.1038/s41598-019-56297-y
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study of Vitamin D Deficiency among Older Adults in China and the United States

Abstract: Vitamin D deficiency is a common health concern worldwide. We aim to compare the prevalence of vitamin D deficiency among older adults (65+) in China and the United States (US). We used data from the 2011 wave of Chinese Longitudinal Healthy Longevity Survey (CLHLS) in China (n = 2180), and 2011–2014 National Health and Nutrition Examination Survey (NHANES) in the US (n = 2283). Serum 25-hydroxyvitamin D [25(OH)D] was measured and a level of under 30/50 nmol/L was defined as vitamin D severe deficiency/deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 48 publications
3
32
1
Order By: Relevance
“…
Fig. 4 a Mean 25(OH)D in the elderly population in the US [ 61 ], Iran [ 62 ], France [ 63 ] and the UK [ 64 ]. Estimated 25(OH)D concentration of elderly in Italy [ 49 51 , 65 ], and Spain [ 52 ].
…”
Section: Results and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…
Fig. 4 a Mean 25(OH)D in the elderly population in the US [ 61 ], Iran [ 62 ], France [ 63 ] and the UK [ 64 ]. Estimated 25(OH)D concentration of elderly in Italy [ 49 51 , 65 ], and Spain [ 52 ].
…”
Section: Results and Interpretationmentioning
confidence: 99%
“…The concentration of 25-hydroxyvitamin D (25(OH)D) among the elderly population in each country was obtained from prior studies [49][50][51][52][53][54][61][62][63][64][65]. CRP, VitD, and demographic variables data of the subjects were pooled from the cross-sectional data from 2009-2010 NHANES, conducted by the National Center for Health Statistics (NCHS), Centers for Disease Control and Prevention (CDC) [55].…”
Section: Methodsmentioning
confidence: 99%
“…Despite these limitations, the present study also has a number of strengths. First, the data was based on a broad age range sample taken from the Korean general population, which represents an ethnically homogeneous group and a geographically homogeneous region; both of these factors are known to affect vitamin D concentrations (45). Second, the analysis was stratified by sex and assessed specific domains of depressive symptoms, extending our understanding of these associations.…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in Europe showed that 13.0% of 55,844 European individuals showed average serum 25(OH)D concentrations of < 30 nmol/L 9 . In China, 30.6% of elderly people have vitamin D deficiency 10 .…”
Section: Introductionmentioning
confidence: 99%